Decomposition of the Kenticha mangano-tantalite ore by HF/H2SO4 and KOH fusion - Tadesse, Bogale; Berhe, G.; Alberto, V.; Yimam, A.; Woldetinsae, G. (Wroclaw University of Science and Technology, 2018)
In this study, the decomposition behavior of Ta and Nb from the mangano-tantalite ore was investigated using HF/H2SO4 mixture and KOH fusion. The effects of reaction time, decomposition temperature, acid and alkaline concentrations, and particle size on the dissolution process were examined. Higher decomposition rates were achieved at 6:2 mol/dm3 ratio of HF and H2SO4, and with the addition of 10 g KOH in the alkali fusion step. In addition, similar trends in decomposition rates between two agents (HF/H2SO4 and KOH) and comparable dissolution performances were observed. The increase in the decomposition temperature initially increased the decomposition rate of manganotantalite for the two systems considered in this study. However, no significant change in the leaching rate of Ta and Nb was observed beyond 50 °C for the HF/H2SO4 system and above 400 °C when using the KOH fusion process. The elemental and compositional analyses of the leached residues using XRF, XRD, and FT-IR spectroscopy indicated that the acid (mixture of HF and H2SO4) decomposition resulted in slightly better dissolution performance for Ta compared with the alkaline fusion method. Overall, the results indicated that KOH can be a suitable alternative decompositio